2017
DOI: 10.18632/oncotarget.23119
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-124 acts as a target for Alzheimer’s disease by regulating BACE1

Abstract: Although large numbers of microRNAs (miRNAs) expressed in Alzheimer disease (AD) have been detected, their functions and mechanisms of regulation remain to be fully clarified. Beta-site Amyloid precursor protein Cleaving Enzyme 1 (BACE1) has been one of the prime therapeutic targets for AD. Here, we identified that miR-124 levels are gradually decreased in AD. In addition, we demonstrated that miR-124 suppresses BACE1 expression by directly targeting the 3′UTR of Bace1 mRNA in vitro. Inhibition of miR-124 sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 20 publications
1
64
0
Order By: Relevance
“…Thus, in the presence of Aβ or hypoxia, miR-124 inhibition provokes an increase in BACE1 levels and, therefore, in the production of toxic Aβ [ 58 ]. Additionally, it is important to highlight that AD patients express low levels of miR-124 [ 59 ].…”
Section: Small Gtpases Of the Ras Familymentioning
confidence: 99%
“…Thus, in the presence of Aβ or hypoxia, miR-124 inhibition provokes an increase in BACE1 levels and, therefore, in the production of toxic Aβ [ 58 ]. Additionally, it is important to highlight that AD patients express low levels of miR-124 [ 59 ].…”
Section: Small Gtpases Of the Ras Familymentioning
confidence: 99%
“…Unexpectedly, we found that the sham-operation (i.e., craniotomy) also affects the miR-124-3p level, indicating that miR-124-3p could be highly responsive to skull and brain surgery. Interestingly, miR-124-3p is also downregulated in the cortex of mice with frontotemporal dementia [64], in the frontal cortex of patients with a behavioral variant of frontotemporal dementia [64], in patients with sporadic Alzheimer disease [65], and in cellular models of Parkinson disease [66] and Alzheimer disease [67]. Together, these findings indicate that miR-124-3p downregulation is broadly connected to brain injury and neurodegeneration, independent of the etiology.…”
Section: Downregulation Of Mir-124-3p Promotes Neurodegenerationmentioning
confidence: 84%
“…A study conducted on human SH-SY5Y cells showed that inhibiting miR-124-3p promoted apoptosis through the AMPK/mTOR pathway [71]. Moreover, miR-124-3p directly targets beta-secretase 1 [65,67], which has a crucial role in the formation of beta-amyloid, indicating that miR-124-3p downregulation contributes to the pathologic hallmarks of Alzheimer's disease.…”
Section: Downregulation Of Mir-124-3p Promotes Neurodegenerationmentioning
confidence: 99%
“…Regulatory factor X1 RFX1 Anti-Aβ deposition Decreased miR-124 represses ApoE-dependent Aβ uptake by targeting and upregulating RFX1 [34] cAMP-response element binding protein CREB Suppressing synaptic plasticity Decreased miR-124 increases the expression of CREB and subsequent BDNF synthesis [45] Tyrosine-protein phosphatase non-receptor type 1 PTPN1 Suppressing synaptic plasticity Downregulating the expression of PTPN1 [46] Beta-site Amyloid precursor protein Cleaving Enzyme 1 BACE1 Anti-Aβ deposition Decreased miR-124 upregulates BACE1 level [47] Caveolin-1 Cav-1 Inhibiting hyperphosphorylation of tau Repressing the expression of Cav-1, which further activates PI3K/AKT/GSK3β signaling pathway [35] Epilepsy cAMP-response element-binding protein 1 CREB1 Anti-neuronal excitability Repressing the expression of CREB1 [32] CCAAT/enhancer-binding protein alpha C/EBPα Anti-epileptogenic Downregulating C/EBPα level, which then inhibits the expression and activity of NRSF [54] Bcl-2-like 13 Bcl2L13 Anti-apoptosis Diminishing the expression of Bcl2L13, which further represses the activation of caspase-3 [55] 2.1. MiR-124 and Ischemic Stroke…”
Section: Neuronal Differentiation Neurovascular Remodelingmentioning
confidence: 99%
“…More importantly, miR-124/BACE1 axis has been considered as a novel target in AD treatment [108]. An et al observed that miR-124 was a negative regulator of BACE1 by directly targeting the 3'UTR of BACE1 mRNA, and the downregulation of miR-124 attenuated Aβ-induced apoptosis and cell viability inhibition in SH-SY5Y cells [47]. Furthermore, Fang et al found the expression of BACE1 could be upregulated on the consequence of the downregulation of miR-124, and further exacerbated amyloid pathology, resulting in the promotion of endogenous Aβ production and Aβ neurotoxicity-induced cell death [93].…”
Section: Mechanisms Of Mir-124 In Alzheimer's Diseasementioning
confidence: 99%